Meguru Panggul and Meguru Kuping Learning Strategy for the Young Generation at the Hari Dwipa Gamelan Group | Strategi Pembelajaran Meguru Panggul dan Meguru Kuping Pada Generasi Muda Di Hari Dwipa Gamelan Group - Swarbawa, I Gusti Gde Diko Nalendra (GHURNITA: Jurnal Seni Karawitan, 2024)
This abstract shows how the meguru panggul and meguru kuping learning strategies are implemented at the Hari Dwipa Gamelan Group Art Studio in Tabanan Regency as an effort to regenerate art practitioners, especially musical art, among school-age children, namely Elementary School to High School. Data collection techniques for implementing the MBKM internship/work practice program are observation, interviews, literature study, and participation in all the Hari Dwipa Gamelan Group Studio program activities. The results of the data analysis are presented in a descriptive narrative. It was concluded that the meguru panggul process occurs when students see the direction and movement of the pelvis in the teacher's hands when playing the piece first. The meguru panggul process runs in harmony with the piece being played. It requires repetition until students combine their understanding with the sound or notes produced by the instrument. When students fully understand the notes in the piece played by the teacher, the meguru kuping process takes place; that is, students with sensitive ears can listen carefully and then pour the piece into the instrument. The meguru panggul and meguru kuping strategies in the learning process are practical and efficient, where students can easily play specific musical patterns.